1997
DOI: 10.1172/jci119329
|View full text |Cite
|
Sign up to set email alerts
|

Development of experimental model of chronic pyelonephritis with Escherichia coli O75:K5:H-bearing Dr fimbriae: mutation in the dra region prevented tubulointerstitial nephritis.

Abstract: Escherichia coli that express Dr fimbriae and related adhesins recognize the common receptor decay accelerating factor. E. coli strains that express adhesins of the Dr family were postulated to be associated with cystitis (30-50%), pregnancy-associated pyelonephritis (30%), and chronic diarrhea (50%). In this study, we investigated the hypothesis that E. coli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
131
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(143 citation statements)
references
References 40 publications
(31 reference statements)
10
131
0
2
Order By: Relevance
“…Our group and other researchers have demonstrated that NO is produced by a variety of uterine cell types, including endometrial epithelium, metrial glands, decidua, myometrial cells, NK cells, and macrophages (6,7,28,38,40). Previous work has also implicated NO as a modulator of uterine infection, including the finding that NO inhibition increased the lethality of experimental intrauterine infection in pregnant rats and that intrauterine infection results in a localized increase in NO synthesis (9,30). These data, together with the observation that the uterine endometrium expresses both NOS II and NOS III (38), suggested that endogenous NO may be involved in the uterine defense against bacterial infection.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Our group and other researchers have demonstrated that NO is produced by a variety of uterine cell types, including endometrial epithelium, metrial glands, decidua, myometrial cells, NK cells, and macrophages (6,7,28,38,40). Previous work has also implicated NO as a modulator of uterine infection, including the finding that NO inhibition increased the lethality of experimental intrauterine infection in pregnant rats and that intrauterine infection results in a localized increase in NO synthesis (9,30). These data, together with the observation that the uterine endometrium expresses both NOS II and NOS III (38), suggested that endogenous NO may be involved in the uterine defense against bacterial infection.…”
Section: Discussionmentioning
confidence: 73%
“…To assess the effects of NO on bacterial invasion and internalization in Ishikawa cells, we used a Dr ϩ fimbriated clinical isolate of E. coli (strain IH11128 [O75:K5:H Ϫ ])or its Dr Ϫ mutant E. coli Dr 14 (9). In addition, we used a recombinant strain, BN406 (the laboratory E. coli K-12 strain carrying plasmid pBJN406), encoding the production of Dr fimbriae, and the recombinant E. coli K-12 strain BN17, containing a transposon insertion mutation in the draE gene (Dr Ϫ phenotype) (9,10,31). Because the cellular receptor of Dr ϩ fimbriated E. coli, DAF, was shown to be expressed in epithelial cells, we initially confirmed the expression of DAF in Ishikawa cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations